Sedimentary model of the Ediacaran Doushantuo cap carbonates from the southeastern margin of the Yangtze Block: Evidence from carbon and oxygen isotopes and elemental geochemistry. Issue 3 (27th November 2022) - Dong, Guoming; Xiong, Guoqing; Dan, Yong; Dong, Jun; Li, Xiaogang; Ma, Long; Deng, Qi; Liu, Chunlai
Abstract : Cap carbonate of the early Ediacaran period represents an abrupt climate shift from severe Marinoan glaciation to a post‐glacial warm environment. Some consensuses on the distinctive negative excursion of δ 13 Ccarb and the origin of its unique sedimentary structures have been reached over the past decades, but certain aspects such as the distribution and redox conditions of cap carbonate still remain controversial. To resolve these issues, we collected detailed samples of the Doushantuo cap carbonate from the Ganlong‐Fanyang section and the Poutoushang reservoir section in the Danzhai County, southeast Guizhou Province, respectively. We conducted carbon and oxygen isotope analysis and trace element analysis in this study. The Ganlong‐Fanyang section was possibly situated in a submarine highland because of its higher carbon isotope than that of the Potoushang section according to the carbon isotopic gradient. Negative carbon isotope excursions at the basal Doushantuo cap carbonate from the two sections correlate well with those from other equivalent cap carbonates and were corresponding to the first one (SN1 or EN1) of the carbon isotopic curve during the Ediacaran period, implying a remarkable global event after the post‐Marinoan glaciation. Geochemical features of trace elements and rare earth elements support an overall oxygen‐rich condition with syn‐depositional or pene‐contemporaneous hydrothermal activities and methane seeps during the deposition of cap carbonate. We reconstruct a new sedimentary model that the Doushantuo cap carbonates were mainly precipitated in relatively shallow‐ to deep‐water shelf environments without disturbance by abundant terrestrial materials, which may be on isolated platforms over the early developed grabens in a deep‐water basinal condition, rather than within the entire oceanic basin. Abstract : A new sedimentary model that the Doushantuo cap carbonates are principally precipitated in relative shallow‐water environments without disturbance by abundant terrestrial materials and maybe on isolated platforms over the preexisted grabens in deep‐water condition. This reconstructed model is consistent with carbon isotopic gradient of contemporary cap carbonate in the southeastern margin of the Yangtze Block.